2011
DOI: 10.1039/c1jm10575b
|View full text |Cite
|
Sign up to set email alerts
|

Apoferritin-camouflaged Pt nanoparticles: surface effects on cellular uptake and cytotoxicity

Abstract: Apoferritin-encapsulated Pt nanoparticles (AFt-Pt) were bio-mimetically prepared by an in situ reduction method in the unique 8 nm spherical cage of apoferritin. The average size of AFt-Pt was 4.3 AE 0.9 nm. The spherical structure of apoferritin remained intact after loading Pt particles in its cavity. Apoferritin coating increased the amount of Pt internalized in HepG2 cells by about three times via receptor-mediated endocytosis. AFt-Pt showed greatly improved biocompatibility compared with polyvinylpyrrolid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…56 Native PAGE analysis of AFt, AFt-Au and AFt-AuFU was also performed as previously reported. 56 Aer gel imaging, the blue protein bands on the gel were separately cut off, digested, 57 and analyzed with ICP-AES for Au.…”
Section: Characterization Of Aft-au and Aft-aufumentioning
confidence: 99%
See 2 more Smart Citations
“…56 Native PAGE analysis of AFt, AFt-Au and AFt-AuFU was also performed as previously reported. 56 Aer gel imaging, the blue protein bands on the gel were separately cut off, digested, 57 and analyzed with ICP-AES for Au.…”
Section: Characterization Of Aft-au and Aft-aufumentioning
confidence: 99%
“…56 Native PAGE analysis of AFt, AFt-Au and AFt-AuFU was also performed as previously reported. 56 Aer gel imaging, the blue protein bands on the gel were separately cut off, digested, 57 and analyzed with ICP-AES for Au. The results showed that the element Au was only detected in the bands of AFt-Au and AFtAuFU while not in the band of AFt, which conrmed the successful incorporation of Au nanoparticles into apoferritin.…”
Section: Characterization Of Aft-au and Aft-aufumentioning
confidence: 99%
See 1 more Smart Citation
“…We speculated that this distinct feature of AFt-CeO 2 was partially attributed to the apoferritin corona, which could potentially promote the cellular internalization process mediated via specific ferritin receptors and prevent the adverse interactions between the nano-CeO 2 and biomolecules in the cytoplasm. 18 Further study (Fig. S6, ESIw) also suggested that the internalization of AFt-CeO 2 was primarily regulated by clathrin-mediated endocytosis (Fig.…”
mentioning
confidence: 99%
“…As an example, platinum is lately being re-examined as a nanoparticle carrier for various biological applications, including cancer [18,19]. It is well-known clinically that platinum is highly nephrotoxic [20,21], and hence one can pre-emptively predict that attempts to translate a platinum-based nanomedicinal formulations from the bench-side to the bed would pose nephro-toxicity challenges.…”
Section: Introductionmentioning
confidence: 99%